Stabilizing layered superlattice MoSe2 anodes by the rational solvation structure design for low‐temperature aqueous zinc‐ion batteries - Zeheng Lv; Yuanhong Kang; Rong Tang; Jin Yang; Guanhong Chen; Yuhan Hu; Pengxiang Lin; Huiya Yang; Qilong Wu; Minghao Zhang; Fenghua Chen; Yueying Peng; et al. (Electron)
Abstract Aqueous zinc‐ion batteries (AZIBs) have attracted widespread attention due to their intrinsic merits of low cost and high safety. However, the poor thermodynamic stability of Zn metal in aqueous electrolytes inevitably cause Zn dendrites growth and interface parasitic side reactions, resulting in unsatisfactory cycling stability and low Zn utilization. Replacing Zn anode with intercalation‐type anodes have emerged as a promising alternative strategy to overcome the above issues but the lack of appropriate anode materials is becoming the bottleneck. Herein, the interlayer structure of MoSe2 anode is preintercalated with long‐chain polyvinyl pyrrolidone (PVP), constructing a periodically stacked p‐MoSe2 superlattice to activate the reversible Zn2+ storage performance (203 mAh g−1 at 0.2 A g−1). To further improve the stability of the superlattice structure during cycling, the electrolyte is also rationally designed by adding 1,4‐Butyrolactone (γ‐GBL) additive into 3 M Zn(CF3SO3)2, in which γ‐GBL replaces the H2O in Zn2+ solvation sheath. The preferential solvation of γ‐GBL with Zn2+ effectively reduces the water activity and helps to achieve an ultra‐long lifespan of 12,000 cycles for p‐MoSe2. More importantly, the reconstructed solvation structure enables the operation of p‐MoSe2||ZnxNVPF (Na3V2(PO4)2O2F) AZIBs at an ultra‐low temperature of −40°C, which is expected to promote the practical applications of AZIBs.